Formation of Grammar Skills for Speech Building - Karimberdiyevna, Radjabova Dildora (Miasto Przyszłości, 2023)
The article discusses the role of ownership of grammatical skills in the formation of speech in a foreign language. The main purpose of teaching grammar in high school is the formation of grammatical skills of students using the implicit, explicit and differentiated approach as one of the most important components of the speech skills of speaking, listening, reading and writing. The ability to intelligently combine the words, phrases change depending on what you want to say at the moment, is one of the most important conditions for the use of language as a means of communication.